Application of Computer Vision in 3D Film. Issue 2 (May 2021) - Yi, Zhenghui
Abstract: As a form of entertainment in our daily life, movies have been a luxury at the beginning and become a normal form now. With the continuous development of The Times, film production technology is also constantly challenging innovation. Especially in recent years, high-end technology has been added to film production in order to make the audience have a better movie experience. The operating principle of 3D movies is simply to make use of the visual differences formed by people's eyes when watching objects, record these differences respectively, and then project them onto people's eyes with computer image technology, so that the audience can have a stereoscopic viewing effect. In the actual film shooting, due to the setting requirements of the scene modeling, a large amount of financial and material resources and manpower are often needed in the production process to create a desired scene, which also increases the production cost of the film, consumes a large amount of shooting time, and even wastes the actor's modeling degree gratuitously. As for the movie scene space, it is actually divided into two parts. One is the real space environment, that is, the scene space in which actors need to perform, and the other is the psychological space of actors in the movie. This paper starts from the computer image processing technology, analyzes the application advantage of this technology in 3D film production, and thoroughly the modern society audience for the ultimate pursuit of the film, from multiple aspects of the development of 3D film and the application of computer image processing technology in 3D film for a detailed explanation.